Investigating the impact of haptotherapy on maternal-fetal attachment in unplanned pregnancies - Tahmineh Atabakhsh; Kobra Salehi; Fatemeh Mohammadi (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Mothers who experience unplanned pregnancies tend to show less maternal attachment to the fetus, which can lead to diminished self-care during pregnancy, and affect well-being of the fetus. Consequently, unintended pregnancies are associated with heightened maternal and fetal consequences due to mothers' negligence. Hippotherapy intervention has emerged as a viable approach to enhance maternal-fetal communication. The ultimate goal of this study was to broaden our current understanding of haptotherapy's impact on maternal-fetal attachment in unplanned pregnancies. MATERIALS AND METHODS: This field trial research was conducted at comprehensive health centers in Isfahan using convenient sampling method. The study consisted of two groups of mothers, each consisting of 33 individuals with unplanned pregnancies between 20 to 24 weeks. The experimental group received haptotherapy intervention for 10 weeks, while the control group received standard pregnancy care. For data collection the participants were given demographic and fertility questionnaire prior to the study, and Cranley's maternal-fetal attachment questionnaire both before and after the study. Moreover, T-test, Mann-Whitney U test, and Chi-square test were used for data analysis. RESULTS: Prior to the intervention, there was no significant difference in the average maternal-fetal attachment scores between the experimental and control groups (P = 0.56). However, a significant increase became apparent after the intervention. The experimental group exhibited a significant improvement in the mean attachment scores compared to their pre-intervention levels (t=-9.20, P = 0<0.001). In contrast, the control group's score remained unchanged, with no significant difference observed (=1.69, P = 0.1). CONCLUSION: Haptotherapy has been found to enhance maternal-fetal attachment in mothers experiencing unplanned pregnancies. This valuable intervention is recommended as an innovative and secure approach in maternal health care services to help reduce the potential complications associated with such pregnancies.